Association between chronic pain, depression, somatization and temporomandibular disorders in a southern brazilian population - Tatiana Bernardon Silva; Rafaela Stocker Salbego; Rachel Seeger Ilha; Thais Fernanda Hahn Dutra; Fernanda Tomazoni; Vitória de Oliveira Chami; Luiza Pereira do Nascimento; Mariana Marquezan (Universidade Estadual de Maringá, 2022)
Introduction: Temporomandibular disorder (TMD) is defined as a set of pathological clinical conditions involving the masticatory muscles, the temporomandibular joint, or both, and the associated structures. It is often associated with chronic headaches, cervical pain, otologic symptoms and may be accompanied by some degree of physical or psychological disability in patients. Objective: To investigate the association of chronic pain-related disability, depression, and somatization with temporomandibular disorders. Methods: It was a transversal study with 275 patients evaluated using the RDC/TMD (Research Diagnostic Criteria for Temporomandibular Disorders). The variables of Axis I (myofascial pain, disc displacement and other joint conditions) and Axis II (chronic pain-related disability, depression and somatization) were crossed using Fischer's Exact Test (p <0.05). Results: Statistically significant association was found among factors of chronic pain-related disability, depression and somatization with myofascial pain diagnosis (p =0.000, p =0.001, p =0.000, respectively), as well as joint conditions (arthralgia, osteoarthritis and osteoarthrosis) (p =0.000, p =0.008, p =0.003, respectively). Conclusion: There is a positive association between chronic pain, depression and somatization (Axis II variables) with and myofascial pain and other joint conditions (Axis I). Disc displacements were not associated to variables of Axis II.